THE TEACHING-LEARNING PROCESS OF ENGLISH BY USING SILENT WAY TO THE THIRD YEAR STUDENTS OF SDN 01 KARTASURA IN 2006/2007 ACADEMIC YEAR (AN ACTION RESEARCH) - ROFIQOH , RUSMALIA (2007)
The objective of the study are to describe the teaching-learning process of English by using Silent Way and its influence to the student's vocabulary mastery, to find the strength and weaknesses of this method. The result of the study is intended to be a little contribution to the teaching-learning process of English. The writer formulates the problem in from of Action Research as follows: "how the teaching-learning process of English using Silent Way and what are the strengths and weaknesses of teaching English using Silent Way". The research was done in SDN 01 Kartasura. As the sample, the writer took 29 students of the third year. The writer conducted treatment to the students in form of the exercises. Based on the data analysis the strengths of teaching-learning process using Silent Way are (1) this method can save a lot of time; (2) the teacher can observe that students can keep the material presented much longer in their mind; (3) the students become more active because the teacher gives more time to talk; (4) the students get more feeling of secure learning through the Silent Way method; (5) this method can improve the students vocabulary; (6) the students can concentrate with the material; (7) the students are more easier to remember that given by the teacher. The weaknesses of teaching-learning process of English using Silent Way are (1) in providing the materials, the writer needs more work preparation of Silent Way than others method (2) this method sometimes makes both teacher and students are frustrated, especially when the students fail to guess the cues provided by the teacher (3) the students tend to rebel against this method (4) dealing with vocabulary only, so it lacks of grammar (5) the students often make an error (6) this method can not be used to teach all aspects of language learning. The conclusion is the teaching-learning process of English using Silent Way in SDN 01 Kartasura is satisfactory. The use of te aching aids in Silent Way method is very appropriate and helpful in teaching-learning process.